Youth employment, agricultural transformation, and rural labor dynamics in Nigeria - Adesugba, Margaret Abiodun; Mavrotas, George (International Food Policy Research Institute, 2016)
Youth employment in developing countries, particularly in connection with agricultural transformation policies in Africa south of the Sahara, has attracted a great deal of attention in recent years. The debate on youth unemployment globally—and specifically in Africa—hinges also on the differential pattern of structural change of economies, which works against the creation of “good” jobs. Although the proportion of unemployed youth in Nigeria has decreased in recent years, the percentage remains high. One recent government effort, the rather ambitious Agricultural Transformation Agenda, was geared (among other things) to promoting employment opportunities for youth in the agricultural sector. The youth employment issue is an important part of the current agricultural policy agenda of the new Federal Government of Nigeria. Against this background, the paper presents a comprehensive national and sectoral growth analysis of youth labor and employment trends in Nigeria, with a particular focus on agriculture and the rural nonfarm economy. It provides insights into the drivers of youth unemployment and underemployment, and discusses the prospects for job creation for youth in the agricultural and the rural non-farm sectors. The paper concludes with a discussion of prospects and policies for enhancing youth employment in the Nigerian agricultural sector, of particular interest to policymakers in Nigeria but also to those interested in youth unemployment in the developing world.